Lichen planus pemphigoides: four new cases and a review of the literature. (20th January 2013) - Zaraa, Ines; Mahfoudh, Anis; Sellami, Myriam Kallel; Chelly, Ines; El Euch, Dalenda; Zitouna, Mohamed; Mokni, Mourad; Makni, Sondes; Osman, Amel Ben
Abstract Lichen planus pemphigoides (LPP) is a rare autoimmune blistering disease. It appears to be combination of lichen planus and bullous pemphigoid. We describe four new cases of LPP and discuss the epidemiological, clinical, pathological, and therapeutic features of this singular association through a review of the 74 published cases within the English literature. We report four cases of LPP (three women aged respectively 47, 51, and 53 years old, and a 53‐year‐old man). All patients presented with bullae on lichenoid and normal skin, predominately on the extremities. The diagnosis was confirmed by immunohistological findings. Our patients were treated with oral corticosteroids with a good response. Our review of the literature of 78 cases of LPP (65 adults and 13 children) showed that it involved adults (mean age: 54 years), with a slight female preponderance. A mean lag time between LP and the development of LPP was 8.3 months. LPP is characterized by developing blisters on lichenoid lesions and on uninvolved skin with more acral distribution of bullous lesions. Involvement of palms and soles was more frequent in children. The diagnosis is based on pathological and immunological confrontation. LPP is usually idiopathic, but some cases were reported in association with various drugs. There have also been reports of association with internal malignancy. Most cases of LPP are successfully treated with systemic corticosteroids. In most cases, the prognosis was good.